Entrepreneurial Motivation for Women Entrepreneurs - Yuliani (Kusuma Negara Business School, 2021)
In Indonesia MSMEs are the dominant economic sector, so they are able to make a large contribution to GDP and employment. In running their business, MSMEs are not only run by men, but also by women. In this study, researchers attempted to obtain comprehensive and in-depth data about the motivations of women entrepreneurs who manage MSMEs in Bandung sub-district, Tulungagung district. Informants who will be involved in this research are restaurant SMEs, retail SMEs and clothing trade SMEs. This research is a type of qualitative research. Data obtained by means of interviews, observations, and documentation. Based on the results of the study, it was concluded that internal motivation in the form of a desire to help family finances was one of the factors driving women to become entrepreneurs. Another factor that drives women SME entrepreneurs is the desire to preserve the business that has been run by their parents, as well as the field of business that is undertaken according to their hobbies.